Pregnancy and Motherhood for Trainees in Anesthesiology: A Survey of the American Society of Anesthesiologists - Kraus, Molly B. (J Educ Perioper Med, 2021)
BACKGROUND: Although approximately half of US medical students are now women, anesthesiology training programs have yet to achieve gender parity. Women trainees’ experiences and needs, including those related to motherhood, are increasingly timely concerns for the field of anesthesiology. At present, limited data exists on the childbearing experiences of women physicians in anesthesiology training. METHODS: In March of 2018, we surveyed women members of the American Society of Anesthesiologists via email. Questions addressed pregnancy, maternity leave, lactation, and motherhood. We analyzed data from a subset of respondents who were pregnant or had children during training and graduated in the year 2000 or later. RESULTS: A total of 542 respondents who completed training in the year 2000 or after reported 752 pregnancies during anesthesia training. A maternity leave had a median length of 7 weeks and did not change significantly over time. During many pregnancies, women felt their leave was inadequate (59.6%) or felt discouraged from taking more time off (65.7%). Pregnancy and associated leave extended graduation from training in 64.1% of cases. In approximately half of pregnancies (51.3%), women met desired breastfeeding duration, with access to designated lactation space decreasing significantly over time (false-discovery adjusted P = .0004). Trainee mothers often felt discouraged from having children (51.6%) or perceived negative stigma surrounding pregnancy (60.3%). These attitudes did not change over time or in relation to female program leadership. CONCLUSIONS: Women anesthesiology trainees commonly face obstacles when attempting to balance work and motherhood. Recent policy changes have addressed some of the challenges identified in our study. Future studies will need to evaluate how these changes have impacted anesthesiology trainees.